2012
DOI: 10.1371/journal.pone.0033398
|View full text |Cite
|
Sign up to set email alerts
|

Whip Use by Jockeys in a Sample of Australian Thoroughbred Races—An Observational Study

Abstract: The use of whips by jockeys is an issue. The current study viewed opportunistic high-speed footage of 15 race finishes frame-by-frame to examine the outcomes of arm and wrist actions (n = 350) on 40 horses viewed from the left of the field. Any actions fully or partially obscured by infrastructure or other horses were removed from the database, leaving a total of 104 non-contact sweeps and 134 strikes. For all instances of arm actions that resulted in fully visible whip strikes behind the saddle (n = 109), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…One study involving detailed analysis of 109 whip strikes (McGreevy et al, 2012) reported that 83% of whip strikes made a visible indentation into the horse's hide and muscling when viewed in slow motion [103]. Additionally, the unpadded section of the whip made contact on 64% of impacts.…”
Section: Empirical Researchmentioning
confidence: 99%
“…One study involving detailed analysis of 109 whip strikes (McGreevy et al, 2012) reported that 83% of whip strikes made a visible indentation into the horse's hide and muscling when viewed in slow motion [103]. Additionally, the unpadded section of the whip made contact on 64% of impacts.…”
Section: Empirical Researchmentioning
confidence: 99%
“…There is no research to indicate that this whip is pain-free, although it is reasonable to assume that, if it were used in the same way and with the same force as a traditional whip, it would have less impact, thereby causing less tissue damage and thus less response with less-intense associated pain in general terms. However, still photographs and high-speed video footage of whip use during Australian flat races indicate that when padded whips are used, both the padded and unpadded sections can come into contact with the horse [ 18 ]. Recent research (since the review) suggests that strikes where the unpadded section of the whip makes contact with the horse are more common than when only the padded section makes contact [ 18 ].…”
Section: Analysis Of the Report’s Findings And Recommendationsmentioning
confidence: 99%
“…However, still photographs and high-speed video footage of whip use during Australian flat races indicate that when padded whips are used, both the padded and unpadded sections can come into contact with the horse [ 18 ]. Recent research (since the review) suggests that strikes where the unpadded section of the whip makes contact with the horse are more common than when only the padded section makes contact [ 18 ]. Additionally, there is recent evidence (since the review) that backhand strikes land with more force than forehand strikes [ 19 ].…”
Section: Analysis Of the Report’s Findings And Recommendationsmentioning
confidence: 99%
“…Subsequent studies have examined the extent to which whip rules are policed [ 6 ], the differences in whip use between apprentice and senior jockeys [ 7 ], jockeys’ attitudes to whip use [ 8 ], and the impact of forehand and backhand whip use [ 9 ]. The padded whip has been regarded as the simple solution to concerns about whipping, but slow-motion videography has demonstrated that such whips strike horses with its unpadded section 64% of the time [ 10 ]. The same study showed that many whip-rule breaches are overlooked and others cannot be observed in any given focal horse, because competing horses obscure the viewer’s line of sight.…”
Section: Introductionmentioning
confidence: 99%